Digital logic design - Holdsworth, B. (Brian); Woods, R. C. (R. Clive) (Oxford [England] ; Woburn, MA : Newnes, 2002)
"Brian Holdsworth's 'Digital Logic Design' is a well-established undergraduate text on digital systems, offering full coverage of the field for undergraduate modules and HND units. It has also proved popular in industry as a reference text. In this new edition, Clive Woods and Brian Holdsworth have fully revised the text to cover all the latest developments in the field and to match current degree module syllabuses. The layout has also been redesigned to make it easier to use, resulting in a book that is highly accessible as well as being fully comprehensive. New, updated and expaded topics in the fourth editon include: EBCDIC, Grey code, practical applications of flip-flops, linear and shaft encoders, memory elements and FPGAs. The section on fault-finding has been expanded. A new chapter is dedicated to the interface between digital components and analog systems." --
Number systems and codes -- Boolean algebra -- Karnaugh maps and function simplification -- Combinational logic design principles -- Combinational logic design with MSI circuits -- Latches and flip-flops -- Counters and registers -- Clock-driven sequential circuits -- Event-driven circuits -- Instrumentation and interfacing -- Programmable logic devices -- Arithmetic circuits -- Fault diagnosis and testing -- Appendix : Functional logic symbols -- Answers to problems -- Bibliography -- Index.
Previous edition: 1993.
Includes bibliographical references (pages 498-499) and index.
Keywords: Digital electronics; Logic design